2022
DOI: 10.1186/s12891-022-05887-5
|View full text |Cite
|
Sign up to set email alerts
|

Based on CT at the third lumbar spine level, the skeletal muscle index and psoas muscle index can predict osteoporosis

Abstract: Background With the increasing number of studies on osteoporosis and muscle adipose tissue, existing studies have shown that skeletal muscle tissue and adipose tissue are closely related to osteoporosis by dual-energy x-ray absorptiometry (DXA) measurement. However, few studies have explored whether the skeletal muscle and adipose tissue index measured at the lumbar spine 3 (L3) level are closely related to bone mineral density (BMD) and can even predict osteoporosis. Therefore, this study aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Skeletal muscle cross-sectional area at the middle level of the T12 vertebral body was calculated using Image J (NIH Image J version 1.52c) software ( Figure 1 ). Relevant studies ( 20 ) have shown that the skeletal muscle threshold ranges from −29HU to 150HU, and the skeletal muscle area was measured within this threshold range in this study. SMI was derived by dividing the calculated area value by the square of the patient’s height (m 2 ).…”
Section: Methodssupporting
confidence: 51%
“…Skeletal muscle cross-sectional area at the middle level of the T12 vertebral body was calculated using Image J (NIH Image J version 1.52c) software ( Figure 1 ). Relevant studies ( 20 ) have shown that the skeletal muscle threshold ranges from −29HU to 150HU, and the skeletal muscle area was measured within this threshold range in this study. SMI was derived by dividing the calculated area value by the square of the patient’s height (m 2 ).…”
Section: Methodssupporting
confidence: 51%
“…We speculate that this may have been influenced by muscle and sample size. The study by Huang et al [42] on the psoas major index at the L3 level included a total of 180 patients, which is a much smaller sample size than that in our study.…”
Section: Discussionmentioning
confidence: 76%
“…Huang et al ( 45 ) found a close correlation between psoas muscle index and BMD in the femoral neck and lumbar spine; a strong association was also found with the FRAX. This study group demonstrated that L3-based muscle index could be a useful tool in the diagnosis of OP, and that psoas muscle index is a better indicator of OP compared to skeletal muscle index.…”
Section: Discussionmentioning
confidence: 92%